An Innovation Approach To Random Fields : Application Of White Noise Theory. - Hida, Takeyuki (World Scientific, 2004)
A random field is a mathematical model of evolutional fluctuatingcomplex systems parametrized by a multi-dimensional manifold like acurve or a surface. As the parameter varies, the random field carriesmuch information and hence it has complex stochastic structure. The authors of this book use an approach that is characteristic:namely, they first construct innovation, which is the most elementalstochastic process with a basic and simple way of dependence, and thenexpress the given field as a function of the innovation. Theytherefore establish an infinite-dimensional stochastic calculus, inpartic.